(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper shows the history of the Enigma machine which was invented by German. It describes the main components of the Enigma and how it works within the initial and final designs. The paper, also, explain the attempts to break the Enigma by Poles and Britain through the weakness that leaded to success. That success was due to many reasons that the bad key management represented the main factor of them